Variation and lexical creation: sociolinguistic study of the metátesis in the creation of jergas of the limeños universitaries - Nieto Salas, Claudia Giselle (2019)
In this article we give an accountof the linguistic variation made by the jargon creation through metathesis. Likewise, the study was focused on the university students from Lima. We elucidate how this process is shown based on variables of age, genre, origin and the faculty where they study, factors thatare contrasted to show how the use of this process varies based on social agents. Finally, we explain the reasons for the utilization of this mechanism on more-familiar relationships between the speakers.